2007
DOI: 10.1007/s11605-007-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track—Different Implications in Pancreatic Surgery

Abstract: Concepts in "fast-track" surgery, which provide optimal perioperative care, have been proven to significantly reduce complication rates and decrease hospital stay. This study explores whether fast-track concepts can also be safely applied and improve the outcomes of major pancreatic resections. Perioperative data from 255 consecutive patients, who underwent pancreatic resection by means of fast-track surgery in a high-volume medical center, were analyzed using univariate and multivariate models. Of the 255 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
0
18

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 42 publications
2
118
0
18
Order By: Relevance
“…Suprapubic catheterisation is superior to transurethral catheterisation if used for DGE is a specific problem after PD occurring in &10-25 % of patients [6,7,9,170]. It may be necessary to insert a nasojejunal feeding tube in a minority of patients.…”
Section: Summary and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suprapubic catheterisation is superior to transurethral catheterisation if used for DGE is a specific problem after PD occurring in &10-25 % of patients [6,7,9,170]. It may be necessary to insert a nasojejunal feeding tube in a minority of patients.…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…Chewing gum has been shown to be safe and beneficial in restoring gut activity after colorectal surgery [176][177][178] Postoperative artificial nutrition Most patients tolerate normal oral intake soon after elective PD. Early oral intake in this patient group has been shown to be feasible and safe [6,144]. A recent large multicentre RCT in patients undergoing only major upper gastrointestinal and hepatopancreaticobiliary surgery (including [80 patients undergoing PD) investigated this issue and concluded that allowing early diet is safe for these patients and that enteral tube feeding did not confer benefit [144].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…In general, mortality rates found in national publications by the year 2012 ranged between 4.3% and 21.9% [8][9][10][11][12][13][14] , being superior to those described in the international literature 3 .…”
Section: Results Results Results Resultsmentioning
confidence: 75%
“…Thus, Berberat et al 8 , Balzano et al 23 and di Sebastiano et al 24 found an average hospital stay of 10, 13 and 10 days, respectively, in series of patients undergoing pancreatectomy. Postoperative fluid restriction, early oral intake and mobilization, effective analgesia and early removal of drains and catheters form, in general, the main recommendations suggested by these and other authors 8,[23][24][25] . While we agree with most of these measures, we do not practice fluid restriction, neither the early removal of abdominal drains.…”
Section: Results Results Results Resultsmentioning
confidence: 96%
“…The introduction of Fast-track programs achieves good results in postoperative outcomes in many surgical pathologies (34)(35)(36)(37)(38)(39)(40)(41). For instance, nephrectomy (42); radical prostatectomy (43); knee and hip prosthesis (44); abdominal aortic aneurysm (36); bariatric surgery (45,46) and lung resections (47) can all be carried out with a mean hospital admittance of less than 4 days and others such as antireflux surgery; suprarenalectomy; cholecystectomy; thyroidectomy; etc, are already carried out in many hospitals in ambulatory care (48,49).…”
Section: Introductionmentioning
confidence: 99%